(untitled) (Semiárida, 2020)
Forty eight crossed pigs DUROC JERSEY x HAMPSHIRE x LARGE WHITE, barrows and gilts, were fed in four treatments, from 28 kg to 95 kg live weight, with four compared diets. Diet 1 based on sorghum as sole grain, diets 2 and 3 based on sorghum and rye from 33% and 66%, respectively, and diet 4 consisting in a control commercial formula. Weight, daily, and feed/gain were not stadiatically different in all treatments, neither on growing nor on fattening periods, notwithstanding the control treatment reached its final weight eight days before. Back fat thickness showed a significant difference (p < 0,05) on account of T3 (66% rye), measurement was made at 95 kg live weight (T3:20,6 mm vs. T1: 23,5 mm; T2: 23,3 mm; and T4: 26,6 mm) Rye diets improved carcass quality as back fat thickness decreased.